Foraminiferal biostratigraphy and palaeoenviron- mental analysis of the basal part of Kalamavka formation (Late Miocene, Ierapetra Basin, Eastern Crete) - Drinia, H.; Antonarakou, A.; Louvari, M. A. (Bulletin of the Geological Society of Greece, 2013)
This work involves a preliminary quantitative analysis of benthic foraminifera for the purpose of the determination of palaeoenvironmental parameters (oxygenation, palaeobathymetry) of the depositional environment of the lower part of the typical section of Kalamavka Formation, in Ierapetra Basin, eastern Crete. The sediments of the studied section contain a rich foraminiferal fauna, mainly dominated by planktonic species. High resolution planktonic foraminiferal record reveals the presence of N. atlantica praeatlantica, N. acostaensis, P. siakensis suggesting an early Tortonian chronostratigraphic age. The quantitative assessment of palaeodepth, suggests deposition at middle shelf to bathyal water depths with moderate organic matter fluxes and elevated oxygen contents of the bottom water, typical for this water depth interval.